2015
DOI: 10.1149/06918.0003ecst
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cathode Current Collector on High Temperature PEM Water Electrolysis

Abstract: The effect of cathode current collectors on polymer electrolyte membrane water electrolysis (PEMWE) was evaluated with I-V and I-high frequency resistance (HFR) characteristics. Results reveal that cathode current collectors can impact water electrolysis performance by controlling the amount of water accumulation there, which is proved with overpotential analysis and systematic operation such as feeding additional nitrogen gas to cathode. The hydrophilic cathode current collectors invited better performance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[27] As a result, the hydrogen gas can transfer into the flow channel with less resistance from the liquid water, and the concentration overvoltage caused by the transport of hydrogen gas is suppressed. [38]. Both the electrolysis voltage and the HFR decrease when the cathode current collector is changed from CC6 to CC4 (case2 and case3, respectively), which can be explained by their HFR difference.…”
Section: Methodsmentioning
confidence: 92%
“…[27] As a result, the hydrogen gas can transfer into the flow channel with less resistance from the liquid water, and the concentration overvoltage caused by the transport of hydrogen gas is suppressed. [38]. Both the electrolysis voltage and the HFR decrease when the cathode current collector is changed from CC6 to CC4 (case2 and case3, respectively), which can be explained by their HFR difference.…”
Section: Methodsmentioning
confidence: 92%
“…[22,55,[85][86][87][88][89]95,127,132,149] While the absence of recirculation on the cathode side was not observed to have an effect on the i-V curve at LT in the case of Ito et al, [150] other studies reported water accumulations in the cathode compartment giving rise to higher voltages. [151,152] Improved performances were in fact noted with nitrogen purging, which prevented water slug entrapments in the flow channel [153] or blockages closer to the membrane region. [88,152] Moreover, an optimal flowrate exists, which removes water to prevent blockage while not being itself a source for membrane dehydration.…”
Section: Operating Conditionsmentioning
confidence: 99%